2005
DOI: 10.1158/1078-0432.ccr-04-2419
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Cyclin D1 Promotes Tumor Cell Growth and Confers Resistance to Cisplatin-Mediated Apoptosis in an Elastase-myc Transgene–Expressing Pancreatic Tumor Cell Line

Abstract: Purpose: Elevated cyclin D1 in human pancreatic cancer correlates with poor prognosis.Because pancreatic cancer is invariably resistant to chemotherapy, the goal of this study was to examine whether the drug resistance of pancreatic cancer cells is in part attributed to cyclin D1 overexpression. Experimental Design: Stable overexpression and small interfering RNA (siRNA)^mediated knockdown of cyclin D1 were done in the newly established Ela-myc pancreatic tumor cell line. Cisplatin sensitivity of control, over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
134
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(158 citation statements)
references
References 42 publications
14
134
1
1
Order By: Relevance
“…Further, increased expression of cyclin D1 has also been reported to contribute to chemotherapy resistance [30]. Our results that GSK-3β increased cyclin D1 expression in ovarian cancer cells support a possibility that GSK-3β is involved in chemotherapy resistance.…”
Section: Discussionsupporting
confidence: 82%
“…Further, increased expression of cyclin D1 has also been reported to contribute to chemotherapy resistance [30]. Our results that GSK-3β increased cyclin D1 expression in ovarian cancer cells support a possibility that GSK-3β is involved in chemotherapy resistance.…”
Section: Discussionsupporting
confidence: 82%
“…Overall, these studies suggested that cyclin D1 exerts a protective effect against drug-induced cytotoxicity. The molecular mechanisms of cyclin D1-mediated chemoresistance, however, remains to be identified (Biliran et al 2005). In agreement with this data, we have demonstrated that T 3 decreased cyclin D1 levels and we can speculate that the increase of the anti-proliferative effect of DDP induced by T 3 is associated to this T 3--dependent cyclin D1 inhibition.…”
Section: Tablesupporting
confidence: 89%
“…The cytotoxic effect of DDP was constant during the first 48 h treatment, but after 72 h the cells began to grow again slowly; this is different from treatment with dFdCyd that showed an increase of cytotoxicity until the end of treatment. Recent studies suggested that the overexpression of cyclin D1 could contribute chemoresistance to DDP therapy in pancreatic cancer cells since dual roles of cyclin D1 in promoting cell proliferation and inhibiting drug-induced apoptosis have been shown (Biliran et al 2005). It was reported that the inhibition of cyclin D1 expression, using an anti-sense strategy, not only suppressed pancreatic cancer cell growth, but also potentiated the anti-proliferative effect of DDP (Kornmann et al 1999).…”
Section: Tablementioning
confidence: 99%
“…Attenuation of cisplatin-induced apoptosis in cyclin D1 overexpressing cells was attributed to the upregulation of Bcl2 and Bcl-xL proteins. However, when the overexpressed Cyclin D1 was downregulated, using antisense RNA, the apoptotic cell death induced by cisplatin was enhanced (Biliran et al, 2005). Furthermore, cyclin D3 interacts with caspase-2, and this interaction lead to an increased caspase activity and apoptosis in HEK 293 cells (Mendelsohn et al, 2002).…”
Section: Pro-and Anti-apoptotic Effects Of Cyclinsmentioning
confidence: 99%